2022
DOI: 10.1097/prs.0000000000009609
|View full text |Cite
|
Sign up to set email alerts
|

Surgeon gender-related differences in operative coding in plastic surgery

Abstract: Background: Numerous studies in the medical and surgical literature have discussed the income gap between male and female physicians, but none has adequately accounted for the disparity. Methods: This study was performed to determine whether gender-related billing and coding differences may be related to the income gap. A 10 percent minimum difference was set a priori as statistically significant. A cohort of 1036 candidates’ 9-month case lists for the American Board of Plastic Surgery over a 5-year span (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The data set used in this analysis did not allow for testing of this hypothesis, as add-on codes and modifiers are not captured. However, the theory is supported by evidence of gender differences in operative coding among plastic surgeons, including using fewer codes per case . Although we could not determine coding differences from the current data set, women might be less likely to use codes that reflect greater complexity, technical difficulty, patient severity, or work intensity, such as modifier 22.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The data set used in this analysis did not allow for testing of this hypothesis, as add-on codes and modifiers are not captured. However, the theory is supported by evidence of gender differences in operative coding among plastic surgeons, including using fewer codes per case . Although we could not determine coding differences from the current data set, women might be less likely to use codes that reflect greater complexity, technical difficulty, patient severity, or work intensity, such as modifier 22.…”
Section: Discussionmentioning
confidence: 92%
“…However, the theory is supported by evidence of gender differences in operative coding among plastic surgeons, including using fewer codes per case. 32 Although we could not determine coding differences from the current data set, women might be less likely to use codes that reflect greater complexity, technical difficulty, patient severity, or work intensity, such as modifier 22. We are not aware of a data set that would allow an analysis of the systematic use of modifier 22, but modifier 22 is rarely used systematically enough to fully explain the aforementioned findings.…”
Section: Discussionmentioning
confidence: 94%
“…The lack of data on add-on codes or modifiers in the CMS dataset precluded further examination of this hypothesis in the current study. However, other investigators have reported gender-related variations in coding practices among different surgical subspecialities, including plastic surgery and neurosurgery, with female surgeons using fewer codes per case. Of note, female surgeons may be less likely to use codes with modifier 22 that indicate more complexity, technical difficulty, patient severity, and work intensity .…”
Section: Discussionmentioning
confidence: 96%